Performer pour durer - Tanguy Dufournet (Recherches Sociologiques et Anthropologiques, 2020)
Choosing to adopt an approach that is both critical and based on the discourses of actors, producers and directors of gay pornographic films, this article seeks to show that the injunctions of pornographic work and the logics of professionalisation produce standards of beauty that mix together in the form of corporeal competencies. This relationship to a specific work tends to produce “the pornographically handsome”, which sometimes profits from potentials on the margins to produce erotic counter-discourses and, at other times, reaffirms prevailing aesthetic standards. Adopting an intersectional interpretation grid allows us to illustrate the paradoxical processes and logics subjacent to this work on “beauty” and bodies, particularly through its relationship to health, food, life rhythms and sports, as well as to pornographic rhythms and rates.